Mejora del proceso de compras y ventas de repuestos en la empresa Laboratorio Diesel Senatinos S.A. - Cárdenas Moza, María Elena (2015)
The purpose of this project is to identify and improve the present buy-and-sell processes of the Laboratorio Diesel Senatinos S.A. Company, so the project develops two possible solutions: (i) to systematize the buy-and-sell processes, and (ii) to train the staff. Once these two possible solutions have been executed, the results shown are satisfactory: (i) the rise of profit, and (ii) the rise of the clients’ satisfaction.